Knowledge Management In Academic Libraries: Librarians In The 21st Century - Asogwa, Brendan E. (Journal of Knowledge Management Practice, 2012)
This paper examines the contributions of librarians in knowledge management, and the implications for academic librarians. A review of relevant literature on contemporary issues in libraries and knowledge management was undertaken, and the current developments in knowledge management and the future for libraries, librarians, and information science professionals were discovered. There is evidence that knowledge management cuts across all spheres of human and organizational activities including libraries and archives. With knowledge management, academic librarians contribute to the improvement of employees’ capacity in knowledge creation; it promotes and strengthens relationships and inter-networking between libraries, librarians, and users. KM creates enablement to mine and extract the wealth of knowledge in library employees. Information technologies, information explosion, multiple formats of information, changing users’ needs and tools have assigned newer roles and responsibilities to academic librarians. It has transformed them from custodians of recorded human intellect to knowledge navigators; they have migrated from librarians to cyberians, knowledge engineers, knowledge gatekeepers, networkers and knowledge brokers. These skills and competencies have to be gripped and imbibed by all knowledge workers or they will become irrelevant in this 21st century.
Keywords: Knowledge management; information technology; Librarian; Academic libraries